Pengaruh Perbandingan Tepung Sagu Dengan Tepung Ulat Sagu (Rhynchophorus ferruginenus) Terhadap Karakteristik Kerupuk - Vortina Panggabean, Adina Juniati; Yusa, Ni Made; Suparthana, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aims to determine the effect of the ratio of sago flour with sago caterpillar flour (Rhynchophorus ferruginenus) on the characteristics of crackers and to determine the ratio of sago flour to sago caterpillar flour which produces crackers with the best characteristics. This study used a completely randomized design consisting of 5 levels of treatment, namely the ratio (100: 0), (90: 10), (80: 20), (70: 30), (60: 40). The formula of sago flour with sago caterpillar flour has not been used for the manufacture of processed products, therefore this formula is used as an ingredient for making crackers. Parameters observed were proximate analysis (moisture content, ash content, fat content, protein content, carbohydrate content), swellability and sensory properties (color, aroma, texture, taste, overall acceptance). The results showed that treatment (90: 10) was the best treatment, with the characteristics of light brown and very attractive, smelled of sago caterpillar, very crunchy and tasted better, while the proximate value, water content of 8,72%, content of ash content is 1,65%, fat content is 0,94%, protein content is 5,25%, carbohydrates are 82,20% and swellability is 10,60%.